Transport and distribution of bottom sediments at Pirita Beach - Soomere, Tarmo; Kask, Andres; Kask, Jüri; Nerman, Robert (Estonian Journal of Earth Sciences, 2007)
The basic factors affecting sediment supply for and transport processes at Pirita Beach, a sandy section of the southeastern coast of Tallinn Bay, are analysed. Observations of bathymetry, sediment properties and sources, sediment transport processes and their changes arising from coastal engineering activities are reported. The mean grain size is about 0.12 mm, with the fine sand fraction (0.063–0.125 mm) accounting for about 77% of the sediments. Coarse sand dominates only along the waterline. The content of coarser sediments is greater in the northern part of the beach. A number of coastal engineering structures have blocked natural sediment supplies. The beach suffers from sediment deficit now and has lost about 400 m3 of sand annually from the dry beach between 1997 and 2005.